A successful pregnancy outcome: post bilateral salphingo-oophorectomy - Adapathya, Sadhana; G., Usha Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A 30 year old nulliparous woman, married for 7 years presented with complaints of lower abdominal pain since a year. Her menstrual history has been regular, associated with dysmenorrhea. She gave a past surgical history of right ovarian cystectomy in view of chocolate cyst noted on diagnostic laparoscopy. Investigations revealed a bilateral complex ovarian cyst and an elevated Ca-125 of 100 units/ml, proceeded with bilateral salphingo-oopherectomy as grade IV endometrioma of both ovaries with frozen pelvis noted. Later, she resumed her menstrual cycles with exogenous estrogen and progesterone. She conceived following a donor oocyte frozen embryo transfer and she delivered a healthy 2.74 kg girl baby with a good Apgar score.